Visualization of the Relationship Between Magnitude and Depth of Earthquakes in Southern Indonesia Through Curve Interpolation - Santoso, Naila Saifana; Inayah, Naya Ajeng; Kamilah, Siti Fitri; Aisyah, Siti Nur (MJI Publisher by PT Mitra Jurnal Indonesia, 2025)
Indonesia in the southern latitudes is one of the tectonically active regions that often experiences earthquakes due to plate subduction activity. This activity causes the accumulation of energy in the subduction zone that can be released at any time in the form of earthquakes with various levels of depth and strength. This study aims to visualize the relationship between depth and magnitude of earthquakes in the region using curve interpolation techniques. Earthquake data was obtained from the BMKG catalog over a period of time, covering a wide range of earthquake events with a fairly wide variation in magnitude and depth. Through this analysis, the general pattern of the relationship between the depth of the earthquake source and the resulting magnitude can be observed, which is then visualized to facilitate interpretation. The visualization results show that there are certain trends that indicate how changes in depth can affect earthquake strength, where earthquakes that occur at a certain depth do not show a tendency that results in greater or smaller magnitudes. This approach is expected to contribute to the understanding of the seismic characteristics of the region.